Genomic characterisation of the Jk(a-b-) phenotype in Thai blood donors - Pramote Sriwanitchrak (2018)
Background. The Kidd (JK) blood group antigens are encoded by the JK gene. The rare Jk(a-b-) phenotype can be caused by homozygosity for a silent JK allele. Currently, JK null alleles have been identified among different populations; however, information on its presence among Thais is not available. Materials and methods. Screening for the Jk(a-b-) phenotype by the urea lysis test was performed in 25,340 blood samples from Thai blood donors. The Jk(a-b-) phenotypes were confirmed by an indirect antiglobulin test (IAT). Additionally, polymerase chain reaction amplification and sequence analysis of the JK gene were performed using previously described methods. Results. Five samples were confirmed as having a Jk(a-b-) phenotype by a urea lysis test and IAT; four of these samples were investigated. Two samples of JK*02 alleles were homozygous for a g > a mutation at the 3′ acceptor splice site of intron 5 of the JK gene, as in previous studies in Asians and Polynesians. Moreover, one sample of JK*02 alleles was homozygous for an 896G > A mutation at exon 9 (Gly299Glu), as in a previous study in Polynesians. Interestingly, missense dual mutations of JK*01 alleles from a female blood donor were identified. The first mutation was 956C > T (Thr319Met) in exon 10, as in a recent study in African-Americans. The second mutation was 130G > A (Glu44Lys) at exon 4, as in previous studies among Caucasians. Conclusion. There are various different molecular bases of the Jk(a-b-) phenotype. This is the first report of JK null alleles among Thais. The information presented in this study could be beneficial in planning genotyping strategies for blood donors and patients. © SIMTI Servizi Srl.